The Relationship between Personality Traits, Value Priorities and White-Collar Crime in Ghana - Tetteh, D.K (University of Ghana, 2014)
Against the backdrop of increasing white-collar crime in Ghana, this study extended the work of Blickle et al. (2006) with a larger sample and within a dissimilar culture, by comparing white-collar offenders concurrently with street offenders and non-offending white-collar professionals on some psychological attributes. Additionally, the study explored the role of personal values in explaining white-collar offending. Data was obtained from 86 employees currently active in Ghanaian work institutions, and 129 white-collar offenders and 86 street offenders (both based on this research’s definition of white-collar and street crime) serving jail terms in prisons. Participants filled out scales that measured conscientiousness (NEO-FFI), narcissism (NPI-16), desire for control (Desirability for Control Scale), self-control (Grasmick et al., I993), value priorities (Portrait Value Questionnaire-40), and social desirability (Marlow-Crowne Social Desirability scale). Overall, the variables Power, Stimulation, self-Direction Hedonism, Desire for control, and Self-control were significant predictors for differentiating among the outcome groups based on their responses to the questionnaire. Whereas value priorities failed to mediate the relationship between traits and white-collar offending, the results seem to suggest that value priorities may moderate same. The results of this study may be beneficial for the selection of personnel in work institutions by way of helping to filter out individuals who are more likely to exploit the organizational, systemic and institutional weaknesses for personal gain. Keywords: white-collar crime; personality traits; value priorities; street crime, Ghana
Thesis (MPhil) - University of Ghana, 2014